L’enfermement, vu de l’intérieur (XXe siècle) - Claire Dumas (Criminocorpus)
From the nineteen century onwards and for a long time, it was a common practice, in all layers of society, to send to confinement girls who were considered not disciplined enough. Sometimes, parents sent their daughter to a Bon Pasteur, on the sole ground she was “bold”. The Bon Pasteur was a reformatory, held by enclosed nuns. Three women, Annie, Michelle, Solange, tell about their youth, shattered by their being sent away for reasons they could not understand. It was in 1929, 1955, 1967, at the Bon Pasteur in Bourges (Cher) and Le Puy en Velay (Haute Loire).In other cases, some catholic families followed the centuries-old tradition, carried on from mother to daughter, to send their prepubescent daughters to convents with the goal to preserve their virginity till they got married. Annick tells about the four painful years she spent in such a confined and coercive environment, in a Norman monastery in Notre-Dame d’Orbec (Calvados), from 1945 to 1949.In the public sector, “preservation” schools with identical goals were experimented. Marguerite, who was put in such an institution by a juvenile court judge, committed suicide a few months before she was due to be released. As a consequence of this tragedy, the institution in Cadillac (Gironde) was definitely closed down in 1951.Christiane, a 20 year old nurse who started her professional life in the Bon Pasteur in Loos (Nord) in 1948, tells about the feeling alienation that affected her, as is common amongst professionals who work in exclusively feminine environment where very troubled girls are secluded and completely isolated from their families.Single motherhood was punished with the same type of repressive treatment, as Evelyne describes it when she lived in a secular maternal home in Clermont Ferrand (Puy de Dôme) in 1967.It is not until the nineteen seventies that a sketchy sexual education for girls started, simultaneously with the legalisation of contraception that came with the revolution in morals.All these stories, but Marguerite’s, were collected by Claire Dumas, caseworker for children and author with the historian Françoise Tétard, of the book: Filles de Justice, du Bon Pasteur à l’Education surveillée, 19e-20e siècle, published in 2009, Beauchesne – ENPJJ editors.